Physical activity achievements of Irish children with disabilities during an adapted physical activity programme. Issue 3 (2nd July 2020) - Tindall, Daniel; Carson, Brian; Tannehill, Deborah; Moody, Brigitte
Abstract : For children and young people with disabilities accumulating the recommended minimum of 60 min per day of moderate-to-vigorous physical activity (MVPA) is difficult to obtain. Much of this has been attributed to a lack of programmes and untrained staff who cannot effectively modify or adapt activities for people with disabilities. Given these barriers, the researchers asked the following question, 'How much activity do children with disabilities receive during a physical activity programme? As such, the purpose of this study was to identify the physical activity achievements of children with disabilities as they participated in a 9-week out-of-school physical activity programme. Participants consisted of twelve children (3 females and 9 males aged 11–15; M  = 13.08) with various disabilities. Data were collected using accelerometers then analysed and separated into the following physical activity intensities; sedentary behaviour, light physical activity, MVPA, vigorous physical activity, very vigorous physical activity, and MVPA and above (≥MVPA), and reported as Mean ± SD. Results indicated that children who completed the programme achieved ≥75% of their recommended daily physical activity requirements. The findings of this study support the assumption that the physical activity programme was effective for children with disabilities in reaching their recommended physical activity levels.